Refleksije vanjske politike Ruske Federacije na međunarodni položaj zemalja Zapadnog Balkana / Reflections of the Russian Federation Foreign Policyon the International Position of Countries of the Western Balkans - Lišinović, Mirza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
The text is a review of Enver Halilović's book "Post-Soviet Geopolitical Space and the Balkans" (Dobra knjiga, Sarajevo, 2012) - a work that arose while the author performed the duty of the ambassador of Bosnia and Herzegovina to the Russian Federation with a residence in Moscow. With a well-designed and well-conceived manuscript, the author has encompassed almost all the most important aspects of the current Russian position and the foreign policy that emerges from it. Of particular importance to the broader reading audience, as well as to the Bosnian society as a whole, are the author's observations on Russian politics and its influence on the Balkans and Bosnia and Herzegovina.